PENERAPAN STRATEGI RECIPROCAL TEACHING PADA PEMBELAJARAN KIMIA UNSUR DENGAN SISWA SEBAGAI MODEL DALAM UPAYA PENINGKATAN HASIL BELAJAR KELAS XII-IA SMA NEGERI 3 SURABAYA - Slamet H.Purwanto; Muslimin Ibrahim; Sri Poedjiastoeti (Universitas Negeri Surabaya, 2017)
This research to implemented of reciprocal teaching strategies with student as a model in the chemical elements to improved student learning outcomes. This research used pretest-postest group design, as the researched target was a XII-iA grade SMA Negeri 3 Surabaya. The instrument used is a sheet implemented plan, tests, and questionnaires. Techniques of data analysis was used to learn the application of the device by calculating the percentage and analysis of student learning outcomes, if student responses used student percentage opinion. The results on this research (1) includes complex plan-oriented learning tools to students reciprocal teaching as a model for 88,95% and categorized well, (2) average student learning outcomes of both groups was 79.47, (3) the results of student responses showed 64% agreed and 32% most agreed if the reciprocal teaching strategies used in the study of chemical elements. Based on the above results the strategy of reciprocal teaching well performed, the results of both groups increased student learning, and as well as the students had a good response on reciprocal teaching strategies in the teaching of chemical elements. Penelitian ini bertujuan menerapkan strategi reciprocal teaching dengan siswa sebagai model dalam materi kimia unsur untuk meningkatkan hasil belajar. Desain yang digunakan dalam penelitian ini adalah pretest postest group design, sasaran penelitian adalah siswa kelas XII-iA SMA Negeri 3 Surabaya. Instrumen yang digunakan terdiri atas lembar keterlaksanaan perangkat, tes, dan angket. Teknik analisis data yang digunakan yaitu menghitung persentase keterlaksanaan, analisis hasil belajar siswa, dan menghitung persentase pendapat siswa. Hasil-hasil dari penelitian ini adalah (1)keterlaksanaan perangkat pembelajaran berorientasi reciprocal teaching sebesar 87,38% dan berkategori baik, (2) rata-rata hasil belajar siswa pada pembelajaran kimia unsur sebesar 79,47, (3) respon siswa sebesar 64% setuju dan 32% sangat setuju jika strategi reciprocal teaching digunakan dalam pembelajaran kimia unsur. Simpulan dalam penelitian ini adalah keterlaksanaan perangkat strategi reciprocal teaching terlaksana dengan baik, hasil belajar siswa meningkat dan siswa memiliki respon yang baik mengenai penerapan strategi reciprocal teaching dalam pembelajaran kimia unsur.